Correlation Between Nutrition Status and Lipid Profile Toward Sexual Satisfaction on Perimenopause Women in Working Area Public Health Centre (PHC) of Bara-Baraya - Jumrah Jumrah; Rosdianah Rosdianah; Syamsuriyana Sabar; Ayu Lestari; Julia Fitria Ningsih (State Islamic University of Sunan Ampel, 2019)
Premenopausal woman is a physiological state that has entered the aging process, which is characterized by decreased ovarian estrogen production. In conditions of estrogen deficiency often arise various debilitating syndrome called premenopausal syndrome women. This study aims to determine the relationship of nutritional status and lipid profile to sexual satisfaction in perimenopausal women. This study used cross-sectional study. The sample in this study is partly perimenopausal women in Puskesmas Bara-baraya total of 37 respondents. Data analysis used chi-square test with Î± = 0.05. It is shown that there was no relationship always connects two things of nutritional status based on BMI (Ï = 0.347).However, the relationship is shown based on the circumference of the abdomen showed a link (Ï = 0.048). Based on cholesterol for the status of lipid, it is shown that there is no association with sexual satisfaction (Ï = 0.006), while based triglycerides, it showed no correlation as well (Ï = 0.571).